Hyalinizing clear cell carcinoma with EWSR1 rearrangement in an 11-year-old girl. Issue 3 (May 2023) - Yamana, Keisuke; Kawahara, Kenta; Kawakami, Fumi; Honda, Yumi; Ishikawa, Kohei; Shinohara, Kosuke; Sakata, Junki; Hirosue, Akiyuki; Yoshida, Ryoji; Kimoto, Natsuko; Nagao, Toshitaka; Mikami, Yoshiki; et al.
Abstract: Hyalinizing clear cell carcinoma is a low-grade salivary gland carcinoma of epithelial origin comprised of malignant cells with clear cytoplasm and often surrounded by hyalinizing stroma. Hyalinizing clear cell carcinoma reportedly occurs in patients with a wide range of ages; however, no reports have been published in children. We herein report a rare case of hard palate hyalinizing clear cell carcinoma with EWSR1 rearrangement in an 11-year-old girl. The patient was referred to our hospital for further evaluation of a growing tumor in the hard palate. After performing biopsy, clear cell odontogenic carcinoma was suspected, although a definitive diagnosis could not be reached. The lesion was clinically suspected to be a salivary gland tumor and resected under general anesthesia. Histopathological evaluation revealed minor salivary gland carcinoma with clear cells and hyalinizing stroma with identification of EWSR1 rearrangement by fluorescence in situ hybridization. Thus, we diagnosed this patient with hyalinizing clear cell carcinoma. Hyalinizing clear cell carcinoma in children is rare, and there has been no evidence of recurrence or metastasis in our patient at 36 months postoperatively.